Trends in Newspaper Coverage of Mental Illness in Canada: 2005–2010. (February 2013) - Whitley, Rob; Berry, Sarah
Objectives: Much research suggests that the general public relies on the popular media as a primary source of information about mental illness. We assessed the broad content of articles relating to mental illness in major Canadian newspapers over a 6-year period. We also sought to assess if such content has changed over time. Methods: We conducted a retrospective analysis of Canadian newspaper coverage from 2005 to 2010. Research assistants used a standardized guide to code 11 263 newspaper articles that mention the terms mental health, mental illness, schizophrenia, or schizophrenic. Once the articles were coded, descriptive statistics were produced for overarching themes and time trend analyses from 2005 to 2010. Results: Danger, violence, and criminality were direct themes in 40% of newspaper articles. Treatment for a mental illness was discussed in only 19% of newspaper articles, and in only 18% was recovery or rehabilitation a significant theme. Eighty-three per cent of articles coded lacked a quotation from someone with a mental illness. We did not observe any significant changes overtime from 2005 to 2010 in any domain measured. Conclusion: There is scope for more balanced, accurate, and informative coverage of mental health issues in Canada. Newspaper articles infrequently reflect the common realities of mental illness phenomenology, course, and outcome. Currently, clinicians may direct patients and family members to other resources for more comprehensive and accurate information about mental illness.